2007
DOI: 10.1562/0031-8655(2001)0730621udoa2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

UV Doses of Americans¶

Abstract: The UV doses of Americans were never measured, but are needed for assessing the risks of UV-related health effects. We calculated these doses using a novel approach. The Environmental Protection Agency's (EPA) National Human Activity Pattern Survey (NHAPS) recorded the activity profiles of 9386 Americans over 24 months to assess their exposure to environmental pollutants, one of which is UV radiation. NHAPS used randomized telephone interviews to get their previous day's minute-byminute activities. From NHAPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 33 publications
(42 reference statements)
6
70
1
Order By: Relevance
“…9,10 The strong seasonal effect on this fraction has also been reported in other studies. 28,29 In an earlier study in subtropical Australia, the personal exposure fraction in winter was found to be more than twice the fraction in summer (6.5% vs. 2.7%).…”
Section: Discussionsupporting
confidence: 84%
“…9,10 The strong seasonal effect on this fraction has also been reported in other studies. 28,29 In an earlier study in subtropical Australia, the personal exposure fraction in winter was found to be more than twice the fraction in summer (6.5% vs. 2.7%).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, we collected UV exposure data from 28 Danish volunteers (13 males and 15 females), median age 39 years (range 4-70) visiting popular sunny holiday resorts in the winter half-year for a median of 7 days (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These subjects were indoor workers from the staff of the department or family or friends of the staff.…”
Section: Study Populationmentioning
confidence: 99%
“…In the continental U.S.A. covering the latitudes 33-45°N, the annual UV doses of Americans were recently estimated based on daily outdoor activity profiles and ambient UV measurements. [1][2][3] These studies are based on the assumption that the same percentage (30%) of terrestrial UV radiation is available for solar exposure during the whole year round. An Australian study examined the annual occupational exposure of outdoor workers to UV radiation (23AE5°S) by personal dosimetry, but did not measure the recreational exposure or the exposure of indoor workers.…”
mentioning
confidence: 99%
“…In a study of the activity profile of over 9000 individuals in the United States over 24 months, it has been estimated that the average UV doses these subjects were exposed to was 25,000 J/m 2 per year. 65 A study of 3449 Canadian adults ([25 years old) reported that 51% of the subjects were exposed to daily sunlight for a duration of between 30 minutes and 2 hours, and 26% were exposed for more than 2 hours. 66 Using personal digital dosimeters, studies in 4 high school students in the New York metropolitan area showed that the average UVB exposure was enough to cause erythema in fair-skinned students.…”
Section: Amount Of Sun Exposure In Daily Activitymentioning
confidence: 99%
“…51,84 However, studies on duration or dose of incidental sun exposure indicated that subjects had more that adequate sun-exposure time or UV dose needed for the current recommended vitamin D level. [64][65][66][67][68][69] The reason(s) for the lack of correlation between these two sets of studies remains to be clarified. Artificial sources of UV vary tremendously in the amount of UVB they contain, and the consumer of that radiation cannot determine that amount from examining these devices.…”
Section: Summary*mentioning
confidence: 99%